2019
DOI: 10.3390/w11020381
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Riparian Restoration Impacts on the Hydrologic Cycle at the Babacomari Ranch, SE Arizona, USA

Abstract: This paper describes coupling field experiments with surface and groundwater modeling to investigate rangelands of SE Arizona, USA using erosion-control structures to augment shallow and deep aquifer recharge. We collected field data to describe the physical and hydrological properties before and after gabions (caged riprap) were installed in an ephemeral channel. The modular finite-difference flow model is applied to simulate the amount of increase needed to raise groundwater levels. We used the average incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 53 publications
4
19
0
Order By: Relevance
“…81 Various watershed restoration techniques, such as in-channel structures including gabions and check dams, can improve water quality and availability and reduce erosion. [82][83][84][85][86] They can also promote vegetation growth in the surrounding area and downstream of the structure. 87,88 The development of a restoration economy that supports these restoration techniques may be important in improving water quality and availability, particularly along streams and perennial water sources where social values are perceived to be the highest.…”
Section: Interpreting the Survey And Solves Resultsmentioning
confidence: 99%
“…81 Various watershed restoration techniques, such as in-channel structures including gabions and check dams, can improve water quality and availability and reduce erosion. [82][83][84][85][86] They can also promote vegetation growth in the surrounding area and downstream of the structure. 87,88 The development of a restoration economy that supports these restoration techniques may be important in improving water quality and availability, particularly along streams and perennial water sources where social values are perceived to be the highest.…”
Section: Interpreting the Survey And Solves Resultsmentioning
confidence: 99%
“…Results of introducing ranchettes portray slight reductions in lateral soil water and ET. The importance of lateral flows and bank storage to maintaining water availability in arid lands is becoming better understood [62,63]. For example, Schreiner-McGraw and Vivoni [64] deemed the connectivity along hillslope-channel pathways an essential control on the streamflow generation and groundwater recharge in arid regions.…”
Section: Discussionmentioning
confidence: 99%
“…Bank storage offers the potential to hold water with returns to the stream occurring over a period of days or weeks, which can reduce flood peaks and later supplement stream flows [73]. Norman and Niraula [66] and Norman et al [63] found that bank storage and lateral flow can be improved in arid land watersheds intentionally, by installing erosion control structures to slow and store water. The potential to guide land-use plans to enhance lateral flows, develop perched aquifers, and recharge groundwater aquifers is of utmost importance in Aravaipa and arid lands in general.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Models were used to identify the best location to attempt recharge in an ephemeral channel, and field data were collected before and after gabions were installed by the BRN. 76 Downstream discharge measurements and a 3-dimensional computer model were used to calibrate a watershed model, simulate flow volumes, and extrapolate findings. In locations with gabions installed, average infiltration behind the gabions increased 10% compared to locations without gabions.…”
Section: Habitat Provisioningmentioning
confidence: 99%